Optimizing sulphur management for sugarcane grown in sulphur-deficient Inceptisols of Odisha, India coastal plains - Majhi, Rajanikanta; Marndi, Satyajit; Sethi, Debadatta; Seth, Pinki; Patnaik, Jyotirekha; Mohanty, Swagatika; Padhan, Kshitipati; Nayak, Anshuman; Swain, Susanta Kumar; Panda, Narayan; Pattanayak, Sushanta Kumar (Frontiers in Soil Science, 2025)
Sugarcane is an important agricultural crop for industrial application especially for sugar industries. The production of sugarcane is declining day by day due to the low soil fertility status. Sulphur (S) is one of the important secondary macronutrients responsible for enhancing the quality and yield of sugarcane by keeping a good fertility status. An experiment was conducted on sulphur management in sulphur deficient sugarcane grow soil. The experiment was laid out for three years with application of S at 60 kg ha-1 through two different sources of sulphur like gypsum and elemental S. The result revealed the highest (0.49%) concentration of nitrogen in the trash was observed in STD+ Gyp15 + 30 + 15 (T10), which also corresponded to the highest nitrogen uptake of 81.3 kg ha⁻¹. The highest (0.21%) phosphorus concentration was estimated in STD+ S015 + 30 + 15(T6), with uptake of 31.71 kg ha⁻¹. The control treatment had the lowest phosphorus and nitrogen uptake in trash. The highest sulphur concentration in the trash (0.19%), resulting in a total sulphur uptake of 31.54 kg ha⁻¹ in STD+ Gyp15 + 30 + 15. The pH decreased in the post-harvest soil after three years of continues cropping irrespective of the treatment’s indicating slight acidification of soil in all the treatments. Irrespective of the treatments compared, available N in postharvest soil decreased from an initial 265 kg ha-1 to 240 kg ha-1 in the control. The organic carbon status was enhanced in all the treatments except STD. The split application of Sat 60 kg h-1 enhanced soil nutrients status with improved microbial activity. The split application of 60 kg S ha-1 at basal, 40 days after sowing and 80 days after sowing enhanced the soil fertility.